An Automated Measurement of Image Slice Thickness of Computed Tomography - S. Sofiyatun; C. Anam; U. M. Zahro; D. A. Rukmana; G. Dougherty (Atom Indonesia, 2021)
Measurement of the slice thickness in computed tomography (CT) is usually made using a special phantom, such as the AAPM CT performance phantom. Images of the phantom are analyzed manually and subjectively. The purpose of this study is to develop an automated system for measuring the slice thickness of the CT image of the phantom using MATLAB software.The CT AAPM performance phantom was scanned by a 128 multi-slice computed tomography scanner (Revolution Evo, GE Healthcare, Waukesha, WI) at a slice thickness of 5 mm with four different phantom orientations and also scanned by a 6 multi-slice CT scanner (Somatom Emotion 6, Siemens AG, Forchheim, Germany) for two slice thicknesses of 5 and 10 mm. Our automatedmethod produced an accurateslice thickness value less than 0.5 mm different from the nominal slice thicknesses and manual measurements. Similar results were obtained when the phantom was rotated. This system is more objective and effective compared to manual systems.